1984
DOI: 10.1111/j.1469-8986.1984.tb00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Lucid, Prelucid, and Nonlucid Dreams Related to the Amount of EEG Alpha Activity during REM Sleep

Abstract: Alpha activity during REM sleep without signs of awakening can discriminate between the blind classification of prelucid, lucid, and nonlucid dreams. Ten good dream recallers were aroused after relatively high or low amplitude REM alpha. The spectral and temporal characteristics of EEG alpha within each REM period were associated with lucidity and other content dimensions. Each type of dream had a reasonably distinct pattern of REM alpha. High amplitude alpha was found to be associated with prelucid dreams and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 28 publications
2
33
0
1
Order By: Relevance
“…This supports the hypothesis that cortical centers involved in language are activated when people speak or hear in dreaming, providing additional evidence that neural systems used in wakefulness are also used in dreaming. Furthermore, other authors [28] reported that the amount of alpha activity in REM sleep was succesfully used to discriminate prelucid dreams (higher power) from nonlucid and lucid dreams. Prelucid experiences are evoked by highly emotional, irrational, or incongruous dreams, and are characterized by the critical attitude toward the dream, questioning its apparent reality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the hypothesis that cortical centers involved in language are activated when people speak or hear in dreaming, providing additional evidence that neural systems used in wakefulness are also used in dreaming. Furthermore, other authors [28] reported that the amount of alpha activity in REM sleep was succesfully used to discriminate prelucid dreams (higher power) from nonlucid and lucid dreams. Prelucid experiences are evoked by highly emotional, irrational, or incongruous dreams, and are characterized by the critical attitude toward the dream, questioning its apparent reality.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings would suggest that alpha activity during REM sleep, which is attenuated (blocked?) [27] or augmented [28], depending on the dream content modality, could be linked to the dream occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Although there is considerable support for each view, there are methodological and theoretical limitations to both that remain to be resolved before it will be clear which process (if indeed either or both) underlies dream reporting on awakening from sleep. Cortical arousal during sleep has been identified by the appearance of α frequency (8)(9)(10)(11)(12) Hz) EEG activity and has been noted by a number of researchers to be associated with mentation reporting. [1][2][3][4][5][6][10][11][12][13] α Activity is high at sleep onset when hypnopompic images occur.…”
Section: There Are Currently Two Broad Classes Of Biological Theory Wmentioning
confidence: 99%
“…Cortical arousal during sleep has been identified by the appearance of α frequency (8)(9)(10)(11)(12) Hz) EEG activity and has been noted by a number of researchers to be associated with mentation reporting. [1][2][3][4][5][6][10][11][12][13] α Activity is high at sleep onset when hypnopompic images occur. 5 Similarly, although sleep terrors occur during slow wave sleep (SWS), EEG indicates increased arousal to that of a wake pattern.…”
Section: There Are Currently Two Broad Classes Of Biological Theory Wmentioning
confidence: 99%
See 1 more Smart Citation